Non-unique solutions of magnetohydrodynamic stagnation flow of a nanofluid towards a shrinking sheet using the solar radiation effect - Ishak, Anuar; Alabdulhadi, Sumayyah; Waini, Iskandar; E. Ahmed, Sameh (MDPI AG, 2023)
This study aimstoinvestigate the magnetohydrodynamicflowinducedbyamovingsurface in a nanofluid and the occurrence of suction and solar radiation effects using the Buongiorno model. The numerical findings are obtained using MATLAB software. The effects of various governing parameters on the rates of heat and mass transfer along with the nanoparticles concentration and temperature profiles are elucidated graphically. Non-unique solutions are discovered for a specific variation of the shrinking strength. The temporal stability analysis shows that only one of them is stable as time passes. Furthermore, raising the Brownian motion parameter reduces both the local Sherwood number and the local Nusselt number for both solutions. It is also observed that increasing the thermophoresis parameter reduces the rate of heat transfer, whereas the opposite trend is observed for the rate of mass transfer.